How the Color Fades From Malus halliana Flowers: Transcriptome Sequencing and DNA Methylation Analysis - Han, Mei-Ling; Yin, Jiao; Zhao, Yu-Heng; Sun, Xue-Wei; Meng, Jia-Xin; Zhou, Jing; Shen, Ting; Li, Hou-Hua; Zhang, Fan (Frontiers in Plant Science, 2020)
The flower color of many horticultural plants fades from red to white during the development stages, shortening the viewing period and affecting ornamental value. We selected Malus halliana, a popular ornamental species, and analyzed the mechanisms of flower color fading using RNA sequencing. Forty-seven genes related to anthocyanin biosynthesis and two genes related to anthocyanin transport were identified; the expression of most of these genes declined dramatically with flower color fading, consistent with the change in the anthocyanin content. A number of transcription factors that might participate in anthocyanin biosynthesis were selected and analyzed. A phylogenetic tree was used to identify the key transcription factor. Using this approach, we identified MhMYB10 as directly regulating anthocyanin biosynthesis. MhMYB10 expression was strongly downregulated during flower development and was significantly positively related to the expression of anthocyanin biosynthesis genes and anthocyanin content in diverse varieties of Malus. To analyze the methylation level during flower development, the MhMYB10 promoter sequence was divided into 12 regions. The methylation levels of the R2 and R8 regions increase significantly as flower color fades; methylation is inversely related to MhMYB10 expression and anthocyanin content. Therefore, we deduce that the increasing methylation activities of these two regions represse MhMYB10 expression.